Growth Experiences and Trust in Government - Timothy Besley; Christopher Dann; Sacha Dray (The Quarterly Journal of Economics, 2026)
Abstract This article explores the relationship between economic growth and trust in government using variation in GDP growth experienced over a lifetime since birth. We assemble a newly harmonized global data set across 11 major opinion surveys, comprising 3.3 million respondents in 166 countries since 1990. Exploiting cohort-level variation, we find that people who have experienced higher GDP growth are more prone to trust their governments, with larger effects found in democracies. Higher-growth experiences are also associated with improved perceptions of government performance and living standards. We find no similar channel between growth experience and interpersonal trust. Second, more recent growth experiences appear to matter most for trust in government, with no detectable effect of growth experienced during one’s formative years, closer to birth, or before birth. Third, we find evidence of a “trust paradox” whereby average trust in government is lower in democracies than in autocracies. Our results are robust to a range of falsification exercises, robustness checks, and single-country evidence using the American National Election Studies and the Swiss Household Panel.